Plant breeding and the nutritive value of crop residues : proceedings of a workshop held at ILCA, Addis Ababa, Ethiopia, 7-10 December 1987 - Reed, Jess D.; Capper, Brian S.; Neate, Paul J. H.; International Livestock Centre for Africa (Addis Ababa, Ethiopia : International Livestock Centre for Africa, 1988)
This is the proceedings of a workshop held at ILCA, Addis Ababa, Ethiopia, 7-10 December 1987. It contains 12 papers on topics related to the use of crop residues as livestock feed in smallholder crop/livestock farming systems, and the role of plant breeding in maintaining or improving their nutritive value. Workshop ses sions covered the role of crop residues as feed resources in smallholder crop/livestock farming systems (3 papers) ; factors limiting the nutritive value of crop residues (3 papers); the effect of genotype and environment on the nutritive value of crop residues (4 papers) ; and perspectives and implications for crop improvement programmes. A fifth section presents reports of working groups on aspects relating to the main workshop sessions, and makes specific recommendations on areas need ing further research and modes for collaboration between crop and livestock research programmes.
Summary in French.
Includes bibliographical references.
occ 17/01/2019
Loans
Keywords: Crop residues - feed; Plant breeding; Animal nutrition; Smallscale feeding; Nutritive value; Mixed farming